The history of Tom Jones a foundling - Fielding, Henry 1707-1754 (The Modern Library of the world`s best books, 1950)
Fielding's classic novel chronicles the adventures of Tom Jones, who was abandoned as an infant and grows into a lusty, imprudent young man. Promising to mend his ways, Tom competes with an abusive rival for the affections of a wealthy squire's daughter, and eventually learns the truth about his identity.